Evaluasi Kelayakan Finansial Usaha Budidaya Ikan Lele Sistem Boster Di Farm Fish Boster Centre, Kabupaten Sidoarjo - Asyifa Anandya; Dwi Sofiati; Mochammad Fattah; Muhamad Andi Saifudin (AKUNTANSI 45, 2023)
Aquaculture contributes to the fisheries sector which is marked by an increase in its production each year. Cultivation of catfish is developing because the type of catfish is easy to cultivate and the high level of public consumption of catfish. One of the innovations in catfish cultivating techniques is through a booster system. This research was conducted at the Fish Farm Booster Center with the aim of analyzing the financial feasibility of the business through short-term financial aspects, long-term financial aspects, and sensitivity analysis. Data analysis uses short-term financial analysis including R/C ratio and BEP, long-term financial analysis includes NPV, Net B/C, IRR and Payback Period, as well as sensitivity analysis by making 3 change scenarios. Based on the research results, this business is said to be profitable and feasible in terms of short-term and long-term financial aspects. While the sensitivity analysis shows that this business is not too sensitive to changes in price increases and decreases in benefits.